High-Content Imaging Reveals Expansion of the Endosomal Compartment during Coxiella burnetii Parasitophorous Vacuole Maturation - Larson, Charles L.; Heinzen, Robert A. (Frontiers in Cellular and Infection Microbiology, 2017)
Coxiella burnetii is an obligate intracellular pathogen and the causative agent of human Q fever. Replication of the bacterium within a large parasitophorous vacuole (PV) resembling a host phagolysosome is required for pathogenesis. PV biogenesis is a pathogen driven process that requires engagement of several host cell vesicular trafficking pathways to acquire vacuole components. The goal of this study was to determine if infection by C. burnetii modulates endolysosomal flux to potentially benefit PV formation. HeLa cells, infected with C. burnetii or left uninfected, were incubated with fluorescent transferrin (Tf) for 0 to 30 minutes, and the amount of Tf internalized by cells quantitated by high-content imaging. At three and five days, but not one day post-infection, the maximal amounts of fluorescent Tf internalized by infected cells were significantly greater than uninfected cells. The rates of Tf uptake and recycling were the same for infected and uninfected cells; however, residual Tf persisted in EEA.1 positive compartments adjacent to large PV after 30 minutes of recycling in the absence of labeled Tf. On average, C. burnetii-infected cells contained significantly more CD63-positive endosomes than uninfected cells. In contrast, cells containing large vacuoles generated by Chlamydia trachomatis exhibited increased rates of Tf internalization without increased CD63 expression. Our results suggest that C. burnetii infection expands the endosomal system to increase capacity for endocytic material. Furthermore, this study demonstrates the power of high-content imaging for measurement of cellular responses to infection by intracellular pathogens.